2020
DOI: 10.1016/j.carbpol.2019.115598
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose/graphene oxide aerogels with enhanced dimensional and thermal stability

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 63 publications
(57 reference statements)
0
35
0
Order By: Relevance
“…When a membrane or film is needed, water is extracted from the BC network by air-drying, hot-and cold-pressing or vacuum-filtration. BC-GO aerogel can be prepared from BC-based hydrogels by freeze-drying or by a supercritical CO 2 method [55][56][57].…”
Section: Processing Routesmentioning
confidence: 99%
“…When a membrane or film is needed, water is extracted from the BC network by air-drying, hot-and cold-pressing or vacuum-filtration. BC-GO aerogel can be prepared from BC-based hydrogels by freeze-drying or by a supercritical CO 2 method [55][56][57].…”
Section: Processing Routesmentioning
confidence: 99%
“…They described a simple way to improve the dimensional and mechanical stability of light and hydrophilic GO-based materials, especially in humid environments. This consisted of reducing the GO, removing functional groups containing oxygen, and consequently decreasing the original hydrophilicity of the material (Pinto et al 2020).…”
Section: Studies and Alternatives For A Hydrophobic Bacterial Cellulosementioning
confidence: 99%
“…The morphology and dimensional stability of 3D bacterial cellulose/graphene oxide (BC/GO) aerogels can be tailored to speci c needs, exploring different reduction strategies for enhanced interfacial hydrophobic-hydrophilic interactions between individual nanoelements (Pinto et al 2020). found that after the carbonization process, the BC/graphene spheres showed excellent capacity to absorb oils and organic solvents due to their highly porous surface, 3D interconnected structure and high mechanical stability, giving good hydrophobicity and elasticity results .…”
Section: Studies and Alternatives For A Hydrophobic Bacterial Cellulosementioning
confidence: 99%
“…Very recently, aerogel-based electrodes have shown promising applications in supercapacitors, since their high specific surface area and well inter-connected three-dimensional (3D) texture can load a high content of active materials [22][23][24]. The cellulose/carbon or cellulose/conducting polymers aerogels can be facilely prepared by the solvent mixing method [25][26][27], and the doping content and 3D microporosity can be tunable during the gelification process [28,29]. For instance, a 3D CNFs/PANI aerogel electrode has been prepared by the supramolecular self-assembly method by mixing of CNFs and PANI nanocomposite suspension.…”
Section: Introductionmentioning
confidence: 99%